Q:

Help 15 pointsFind the product. (6g – 5h)2(a) 36g2 – 25gh + 25h2(b) 36g2 – 60gh + 25h2(c) 36g2 – 60gh – 25h2(d) 36g2 + 25h2

Accepted Solution

A:
Answer:36 g^2 + -60 g h + 25 h^2  thus: BStep-by-step explanation:Expand the following: (6 g - 5 h)^2 (6 g - 5 h) (6 g - 5 h) = (6 g) (6 g) + (6 g) (-5 h) + (-5 h) (6 g) + (-5 h) (-5 h): 6×6 g g - 5×6 g h - 5×6 h g - 5 (-5) h h 6 g×6 g = 6×6 g^2: 6×6 g^2 - 5×6 g h - 5×6 h g - 5 (-5) h h 6×6 = 36: 36 g^2 - 5×6 g h - 5×6 h g - 5 (-5) h h 6 (-5) = -30: 36 g^2 + -30 g h - 5×6 h g - 5 (-5) h h -5×6 = -30: 36 g^2 - 30 g h + -30 h g - 5 (-5) h h -5 h (-5) h = -5 (-5) h^2: 36 g^2 - 30 g h - 30 h g + -5 (-5) h^2 -5 (-5) = 25: 36 g^2 - 30 g h - 30 h g + 25 h^2 g h (-30) + h g (-30) = -60 g h: Answer:  36 g^2 + -60 g h + 25 h^2